Managing Metastatic Melanoma in 2022: A Clinical Review. Issue 5 (8th May 2022) - Switzer, Benjamin; Puzanov, Igor; Skitzki, Joseph J.; Hamad, Lamya; Ernstoff, Marc S.
Abstract : Cutaneous melanoma remains the most lethal of the primary cutaneous neoplasms, and although the incidence of primary melanoma continues to rise, the mortality from metastatic disease remains unchanged, in part through advances in treatment. Major developments in immunomodulatory and targeted therapies have provided robust improvements in response and survival trends that have transformed the clinical management of patients with metastatic melanoma. Additional advances in immunologic and cancer cell biology have contributed to further optimization in (1) risk stratification, (2) prognostication, (3) treatment, (4) toxicity management, and (5) surveillance approaches for patients with an advanced melanoma diagnosis. In this review, we provide a comprehensive overview of the historical and future advances regarding the translational and clinical implications of advanced melanoma and share multidisciplinary recommendations to aid clinicians in the navigation of current treatment approaches for a variety of patient cohorts.